Attitudes of future physicians and pharmacists towards collaboration and dispensing separation policy / Nur Azmiah Zainuddin - Zainuddin, Nur Azmiah (2014)
Background: Collaboration between physicians and pharmacists is one of the strategies for improving healthcare delivery. Strong working relationships are believed to improve patient outcomes. There appears to be little to no collaborative working relationship between physicians and pharmacists in the private, as well as public sector, hence it is crucial to develop and understand precursors of developing necessary collaborations. This study aims to validate an instrument that measures attitudes toward collaboration; to measure the perceptions of interprofessional learning and dispensing separation policy among pharmacy and medical students. Methodology: Data were collected using three sets of questionnaires; Scale of Attitudes Toward Pharmacist-Physician Collaboration (SATP²C), Multiprofessional Shared Learning Questionnaire (MSLQ), and Dispensing Separation Questionnaire (DSQ). The questionnaires were self-administered by the final year medical and pharmacy students in Universiti Teknologi MARA (UiTM) Puncak Alam by a convenient sampling. Results: The response rates were 62% and 92% from medical and pharmacy students respectively. The factor analysis confirmed the validity of SATP²C questionnaire thus, can be use for our local students. Majority of the students reported positive attitudes towards interprofessional shared learning however divergent agreements were observed for dispensing separation policy. Conclusion: Pharmacy students showed more positive attitudes toward pharmacistphysician collaboration and interprofessional education. Conflicting opinions regarding dispensing separation policy entails for interprofessional education system to be formulated.